Tradisi Reformed, Kultur Gereja Kristen Sumatera Bagian Selatan, dan Kitab Suci - Yosafat Agung Prabowo (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2022)
This article is motivated by the anxiety to see how Reformed tradition seems less relevant or even irrelevant in Gereja Kristen Sumatera Bagian Selatan (GKSBS). This article thesis is a Reformed tradition, which is relevant to GKSBS, as it is placed in a “critical-appreciative dialogue with nglari and mandiri culture” and “in an authority dialogue with Holy Scripture”. To support the thesis, the writer “describe factual encounter” and “imagine critical appreciative dialogue” between Reformed tradition and Gereja Kristen Sumatera Bagian Selatan (GKSBS) nglari and mandiri culture, and then place them in authority dialogue with Holy Scripture. The results have found that there are meeting points and complementary potency between a boarder Reformed tradition and nglari culture eventhough the nglari culture defeats some Gereformeerd tradition aspects. The writer also found in many aspects, not only in Gereformeerd tradition, that affirms with mandiri culture each other, but also in a broader Reformed tradition which is able to critize the culture each other.  However, both Reformed tradition and GKSBS culture still need to be reformed according to the Holy Scripture.